The Influence of Capital Adequacy, Profitability, and Loan Growth on Non-Performing Loans a Case of Tanzanian Banking Sector - Malimi, Kilugala (International Journal of Economics, Business and Management Studies, 2017)
This study had two central objectives, compliance of capital adequacy and non-performing loan ratios prudential requirement and analysis on the influence posed by Capital Adequacy, Profitability, and Loan Growth on Non-Performing Loans. Banking sector ratios as reported by the supervisory authority (Bank of Tanzania) were used for the purpose of this study. The banking sector ratios show that commercial banks in Tanzania had strong Capital adequacy ratio greater the 10% required by the Bank of Tanzania. However, the banking sector failed to meet non-performing loans 5% threshold. On the hand, when regression analysis was used to study the influence, it was found that, capital adequacy, profitability posed insignificant influence on non-performing loans whereas loan to asset ratio and interest margin had a significant influence.